The teaching librarian Web 2.0, technology, and legal aspects - Helge, Kris; McKinnon, Laura F. (Chandos information professional series, 2013)
Librarians need to utilize web 2.0 tools to generate rich-text learning environments, creating enriching, challenging, and supportive learning platforms for students. The Teaching Librarian shows how to utilize wikis, mindmaps, and Second Life to improve pedagogy for librarians. This title covers how to obtain administration approval to implement web 2.0 tools, how to deal with and prevent technological glitches, and remain aware of relevant legal issues in the UK and the USA. The book also outlines how to create learning interfaces that meet the needs of nontraditional students. The six chapters cover key areas of pedagogy and web 2.0, including: the relevance of LibGuides and its uses for pedagogy; using cloud computing and mobile apps in teaching; teaching with Wikis, Second Life, and Mind Maps; practical issues with web 2.0 technology; and a chapter on the legal issues surrounding the use of web 2.0 for pedagogy. Provides examples of empirical research that tests the implementation of Second Life, wikis, and mind maps in pedagogical scenariosOffers research that enables pedagogy while remaining aware of and complying with current United Kingdom and US legal frameworksProvides case studies and empirical research showing how to gain acceptance of technology in academic environments.